Angular resolution of an antenna array with two incoming coherent signals, - Shejbal, Tomáš; Bezoušek, Pavel (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The paper deals with an angle of arrival (AoA) adaptive estimation in the case of coherent signals incident to an antenna array. The used methods are: forward/backward averaging and forward/backward spatial smoothing. The assumed signal model and mentioned methods are described and analysed. To prove the theoretical analysis measurements of a 4 element antenna array with an offline signal processing was performed and the simulation and measurement results are compared and discussed.
Rozlišení anténní řady v úhlu pro dva příchozí koherentní signály
Keywords: Angular; resolution; antenna; array; with; two; incoming; coherent; signals; Rozlišení v úhlu, adaptivný metoda, zpracování signálu, anténní pole